Evaluation of The Completeness of Electronic Medical Records In Supporting Reporting of The Top 10 Diseases of Inpatients At Majalengka Regional Hospital - Nova Oktaviani Rahayu; Intan Pujilestari (International Journal of Health and Pharmaceutical (IJHP), 2026)
The completeness of Electronic Medical Records (EMR) is one of the important factors that determine the quality of health information and the accuracy of reporting the top 10 diseases in hospitals. This study aims to evaluate the completeness of the EMR in inpatients in supporting the reporting of the top 10 diseases at Majalengka Regional Hospital, identify the top 10 diseases, analyze EMR support for reporting, and identify factors that influence EMR incompleteness. The study used a mixed method with a quantitative approach as the dominant method and a qualitative approach as a complement. The quantitative population amounted to 1,813 EMR documents of inpatients in the fourth quarter of 2025 with a sample of 328 documents determined using simple random sampling. The qualitative population consisted of medical record officers. The research instruments included a checklist, interview guide, and documentation study. Quantitative data were analyzed descriptively using percentages, while qualitative data were analyzed through narrative writing. The results showed that most EMR components were complete, but incompleteness was still found in the informed consent, history taking, diagnosis, and operation report. The EMR supports the compilation of top 10 disease reports through the Zicare application, but reporting quality is still affected by completeness of documentation, diagnostic accuracy, workload, healthcare provider coordination, and system limitations. This study concludes that the EMR has supported the reporting of top 10 diseases at Majalengka Regional Hospital, but improvements in documentation quality and strengthening of the EMR management system are still needed to produce more accurate and high-quality reports.